Application of molecular approach in combination with providing treatment and control measures for combating Babesia bovis and Babesia bigemina infections in small scale livestock farms in Thailand - Nutsuda Klinkaew; Pairpailin Jhaiaun; Giang Thi Nguyen; Ruttayaporn Ngasaman; Domechai Keawnoi; Niorn Rattanapob; Pipat Arunvipas; Meyanee Kanjanaphan; Nuttapon Manojai; Suwitcha Panchakhan; Julaluk Jaiboon; Piyavadee Numnual; et al. (Parasite Epidemiology and Control)
Bovine babesiosis is a tick-borne disease that is caused by apicomplexan protozoan parasite in the genus of Babesia. Babesia infections affect cattle health, reduce milk and meat production and lead to economic losses in tropical and subtropical countries. Babesia parasites are difficult to diagnose in the early stage of infections during low parasitemia and asymptomatic conditions led to the lack of treatment and control at the early stage of infection. This study aimed to integrate a molecular tool for the detection and genetic characterization of Babesia (B.) bovis and B. bigemina in small-scale livestock farming in Thailand, and to study the risk factors association with Babesia infections in small scale livestock farms in Thailand. This study was conducted in four regions of Thailand between June 2023 and January 2024. Dairy and beef cattle blood samples were collected, genomic DNA were extracted and nested PCRs were performed. Data associated with Babesia infections were collected using a semi-structured questionnaire and interview. Nested PCR targeting B. bovis spherical binding protein 4 (SBP4) and B. bigemina rhoptries associating protein 1a (Rap1a) genes were performed and direct sequencing and phylogenetic analysis were conducted. Risk factors association with Babesia infections were analyzed. PCR results, chemotherapeutic treatment options, and vector control suggestions were also reported to local veterinarians and farmers within 14 days. A total of 964 livestock blood samples were collected from 126 small scale farms in four regions of Thailand. B. bovis infection was predominant in buffalo (31.25 %), followed by dairy cattle (11.44 %) and beef cattle (7.47 %). B. bigemina infection was predominant in goats (53.33 %), followed by beef cattle (25.33 %) and dairy cattle (8.88 %). Mixed infection was also detected in beef and dairy cattle at 2.09 % and 1.58 %, respectively. Molecular characterization of B. bovis SBP4 and B. bigemina RAP1a sequences showed that B. bigemina and B. bovis Thai isolates were closely related among geographical areas and shared genetic similarity among different hosts but were genetically distinct from B. bigemina and B. bovis from other countries. Risk factor analysis identified five factors associated with B. bovis infection and one factor associated with B. bigemina infection in small-scale livestock farming in Thailand. All the farmers were very satisfied with the integrative approach. This study implemented sensitive and specific nested PCR methods for the detection of Babesia in livestock. Applying an integrative approach by providing a sensitive diagnostic tool for identification of the infected animals and providing proper treatment and control measures to local farmers help combating babesiosis in small scale livestock farms.